Ehrlichia and Anaplasma in Florida - Cynthia C. Lord; C. Roxanne Rutledge Connelly (EDIS)
Ehrlichia and Anaplasma are related bacterial genera containing species that can cause disease in both humans and domestic animals. The diseases are often referred to simply as ehrlichiosis or anaplasmosis, but there are multiple species of bacteria that can cause different disease symptoms and have different vectors. This revised 3-page fact sheet was written by Cynthia C. Lord and C. Roxanne Rutledge Connelly, and published by the UF Department of Entomology and Nematology, March 2012.